The Economics of Roller Ginning Technology and Implications for African Cotton Sector - Estur, Gerald; Gergely, Nicolas (World Bank, Washington, DC, 2017)
This report is the final product of a follow-up study undertaken after the completion of the comparative analysis of organization and performance of cotton sectors in Sub-Saharan Africa, a study published by the World Bank in 2008. The objective of this complementary study is to assess the advantages and disadvantages of the main available technologies to separate the lint from the raw cotton, roller ginning and saw ginning, and carry out an economic analysis of the respective benefits of these two technologies for cotton producing countries of Sub-Saharan Africa. The study shows that the choice of ginning technology is an important factor of performance and is in turn influenced by the cotton sector structure. The type of ginning technology also has an impact on lint quality, and, as roller ginning is less damaging to the fiber than saw ginning, it can generate a price premium. The overall economic advantage of roller gins vs. saw gins appears to be significant in the Sub-Saharan African context, and likely to increase in the future as the demand for quality is becoming more and more stringent. Thus, although there are technical and organizational issues to address in order to fully capture the benefits of the technology, the introduction of roller ginning is likely to improve the competitiveness of African cotton and facilitate the transition towards more competitive cotton sectors.